Relationships of tensile strength with crosslink density for the high‐carbon black‐filled EPDM compounds with various softeners. Issue 8 (23rd July 2021) - Tu, Jieyun; Shi, Xinghui; Jing, Yuanrong; Zou, Huimin; Kadlcak, Jakub; Yong, Zhanfu; Liu, Susu; Liu, Guangyong
Abstract: Equilibrium swelling and rheological tests were adopted to systematically investigate the effects of softener type and dosage on the crosslink densities. The results turned out that the chemical crosslink density could be distinguished from the physical crosslink density by comparing the results of equilibrium swelling and rheological tests. The liquid butadiene (LB) as a softener leads to the greatest reduction in crosslink density, followed by polyethylene wax (PW) and paraffinic oil (PO). The tensile strength decreases with increasing PO content while shows peak values with increase of LB and PW contents. The dependencies of chemical crosslink density on the aging time under 150°C are quite different for the three softeners, which can be expected from the double crosslinking networks consisting of small softener and large main crosslinking networks. Further investigation has been performed to correlate the tensile strength with chemical crosslink density of ethylene propylene diene monomer elastomer vulcanizates. Three different linear relationships can be obtained for the softeners independent of the aging time. It can now be expected from this study that the role of some new softeners in rubber compounds is not only confined to plasticization but also forms crosslinking networks in the peroxide‐cured rubbers. Abstract :